1976
DOI: 10.1111/j.1532-5415.1976.tb03260.x
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Case of Sarcoidosis Fever

Abstract: Febrile episodes in a male patient with coronary artery disease and arteriovenous malformation of the spinal cord had been attributed to urinary-tract infections and pulmonary atelectasis. The autopsy findings, however, indicated that the fever may have been related to sarcoidosis which had not been detected pre mortem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Other reviews of large series of sarcoidosis [3-6J found the incidence of fever to vary from 3 to 40°/o, but in most cases the fever was low grade and associat ed with skin and eye involvement. Two iso lated case reports were published lately [7,8] on long-standing high fever as initial clin ical manifestation of sarcoidosis. In 1 case, generalized sarcoidosis was diagnosed only in autopsy [7] and the other [8] had suf fered from fever, chilly night sweat and weight loss for 13 months before sarcoidosis was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews of large series of sarcoidosis [3-6J found the incidence of fever to vary from 3 to 40°/o, but in most cases the fever was low grade and associat ed with skin and eye involvement. Two iso lated case reports were published lately [7,8] on long-standing high fever as initial clin ical manifestation of sarcoidosis. In 1 case, generalized sarcoidosis was diagnosed only in autopsy [7] and the other [8] had suf fered from fever, chilly night sweat and weight loss for 13 months before sarcoidosis was diagnosed.…”
Section: Discussionmentioning
confidence: 99%